Business Losses and Force Majeure in Murabahah Disputes (Legal Analysis of Supreme Court Decision No. 179 K/Ag/2017) - Permatasari, Wulandari Dewi; Isman, I; Hakim, Lukmanul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This paper analyzes Supreme Court Decision No. 179 K/Ag/2017 on murabahah financing disputes. It focuses on force majeure, the principle of pacta sunt servanda, and good faith in assessing debtor business losses. This analysis helps explain the Supreme Court's decision within the framework of Islamic economic law. The method used is philosophical jurisprudence, with a descriptive-analytical approach to the decision. This approach clarifies how judges consider force majeure, pacta sunt servanda, and the good-faith standard. The study found that the force majeure argument was rejected because there was no direct causal link between the BPJS policy and the business losses. As a result, pacta sunt servanda still applies. The debtor's good faith was not enough to exempt them from murabahah payment obligations. Theoretically, the decision affirms that the limits of force majeure in murabahah contracts reinforce the principles of pacta sunt servanda and good faith. The practical implication is that the decision guides Islamic banking practitioners and customers. Proof of force majeure must include direct causality between regulatory uncertainty and business risk. Without this proof, the judge will apply the principles of pacta sunt servanda and good faith. This study contributes to the development of Islamic contract law by emphasizing the consistency of judicial interpretations of extraordinary circumstances. It highlights the importance of the burden of proof in establishing the existence of force majeure in Islamic nancing disputes. By strengthening legal certainty, this decision promotes responsible risk management and contractual compliance in murabahah transactions. Ultimately, the ruling supports a balance between justice and legal certainty in resolving disputes under Islamic economic law.